The task of the key stakeholders values harmonizing in a construction project in the context of strategic communications with them - Vedmiediev, Oleksii (КНУБА, 2025)
The research objective is defined, it is to increase the effectiveness of interaction with stakeholders of construction projects. Scientific sources on stakeholder engagement and value-based project management are analyzed. Typical key stakeholders of a construction project are identified, their brief characteristics are provided. A conceptual model of balancing the values of key stakeholders of a construction project and the target function of harmonizing strategic communications with key stakeholders of a construction project are proposed. Prospects for further research in the chosen direction are outlined. Conclusions are formulated.
Keywords: project management; construction project; key stakeholders; values; strategic communications